Tumor suppressor p53 negatively regulates glycolysis stimulated by hypoxia through its target RRAD - Zhang, Cen (Impact Journals LLC, 2014)
Cancer cells display enhanced glycolysis to meet their energetic and biosynthetic demands even under normal oxygen concentrations. Recent studies have revealed that tumor suppressor p53 represses glycolysis under normoxia as a novel mechanism for tumor suppression. As the common microenvironmental stress for tumors, hypoxia drives the metabolic switch from the oxidative phosphorylation to glycolysis, which is crucial for survival and proliferation of cancer cells under hypoxia. The p53's role and mechanism in regulating glycolysis under hypoxia is poorly understood. Here, we found that p53 represses hypoxia-stimulated glycolysis in cancer cells through RRAD, a newly-identified p53 target. RRAD expression is frequently decreased in lung cancer. Ectopic expression of RRAD greatly reduces glycolysis whereas knockdown of RRAD promotes glycolysis in lung cancer cells. Furthermore, RRAD represses glycolysis mainly through inhibition of GLUT1 translocation to the plasma membrane. Under hypoxic conditions, p53 induces RRAD, which in turn inhibits the translocation of GLUT1 and represses glycolysis in lung cancer cells. Blocking RRAD by siRNA greatly abolishes p53's function in repressing glycolysis under hypoxia. Taken together, our results revealed an important role and mechanism of p53 in antagonizing the stimulating effect of hypoxia on glycolysis, which contributes to p53's function in tumor suppression.